(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: Imperforate hymen (HI) is the most common obstructive anomaly of the female genital tract. When present in adolescents, it generates a progressive accumulation of blood in the vaginal cavity, and with it, symptoms such as: abdominal and pelvic pain, often cyclical, low back pain and urinary retention, which can progress to anuria and hydronephrosis. Case report: A 13-year-old girl was referred to our service with a 12-day history of progressive abdominal pain, an abdominal-pelvic mass and acute urinary retention. She had elevated CA125 and CA19.9 and had an initial ultrasound diagnosis of an ovarian mass. She did not have dysuria, vomiting or fever and reported menarche for 2 months, in small amounts, without new episodes of menstruation. The diagnosis of HI was made by the presence of hematocolpos on a new ultrasound, confirmed by physical examination. Subsequently, she underwent hymenotomy with emptying of the hematocolpus. The patient evolved with total improvement of pain and spontaneous urination. CA 125 and CA 19.9 are markers widely used for screening for ovarian and pancreatic cancer, among others, but they also increase in benign conditions. Conclusion: Most publications related to HI are descriptions of clinical presentations, complications and treatment. This case is one of the few in the literature that demonstrates HI associated with increased levels of CA 19.9 and CA 125. The mechanism that leads to this increase may be inflammation of the epithelial tissues (peritoneal, vaginal and uterine), generated by obstruction of the desquamation of tissue. Late discovery of an imperforate hymen can cause pain, infection, hydronephrosis, endometriosis, and infertility.